Development of Sustainable PPE for Higher Threat Clearance Operations by Humanitarian Organisations - Brown, Laura (Cranfield University, 2022)
Humanitarian demining is a hugely important task being undertaken all over the world with 59 countries and territories still contaminated by landmines and unexploded ordnance as of 2020. Personal Protective Equipment (PPE) for demining has traditionally been designed to protect against threats from legacy mines. However, over the last decade there has been an increase in the charge sizes used in these devices. It is currently unknown how the current PPE will perform and interact with these larger threats. Therefore, there is a need to understand whether improvements need to be made to both the standards used and the PPE itself. PPE that would be used by the police and militaries for these higher charge threats, e.g. IEDs and UXO, is highly developed, however it is extremely expensive and would be inappropriate for the demining industry. This project is therefore working to bridge the gap and help produce an effective and low-cost PPE solution that can be used by the humanitarian sector.
Keywords: Blast; Armour; Demining